RESPON PERTUMBUHAN JAGUNG TERHADAP PEMBERIAN PUPUK-PUPUK NPK, UREA, SP-36, DAN KCL - Titah, Tilda; Purbopuspito, Joko (Universitas Sam Ratulangi, 2016)
ABSTRACT Potted trial for understanding Maize (Zea mays, L.) growth responses on the given dosage of 100 kg N/ha of NPK and Urea, 100 kg P/ha of SP-36, and 100 kg K/ha KCl fertilizers growing on Latosol Kalasey was conducted in six replicates until the plants reaching 8 weeks old at the backyard of Soil Department building. Plant height and number of mature leaves increased significantly with age of Maize plants, but the plant responses on given fertilizers did not significantly different.Â Fresh weight dan oven-dry weight of Maize stalk did also show similar trend due to given fertilizers; however, application of singular fertilizers, such as: Urea, SP-36 and KCl gave relatively higher results in contrast to the compound NPK fertilizer.Â Urea tend to increase succulence of Maize plants. Keywords: maize, growth response, NPK, Urea, SP-36, KCl, fertilizers